Preclinical Challenges in Proton Minibeam Radiotherapy: Physics and Biomedical Aspects - Datzmann, Gerd; Sammer, Matthias; Girst, Stefanie; Mayerhofer, Michael; Dollinger, Günther; Reindl, Judith (Frontiers in Physics, 2020)
The concept of spatial fractionation in radiotherapy was developed for better sparing of normal tissue in the entrance channel of radiation. Spatial fractionation utilizing proton minibeam radiotherapy (pMBRT) promises to be advantageous compared to x-ray minibeams due to higher dose conformity at the tumor. Preclinical in-vivo experiments conducted with pMBRT in mouse ear models or in rat brains support the prospects, but the research about the radiobiological mechanisms and the search for adequate application parameters delivering the most beneficial minibeam therapy is still in its infancy. Concerning preclinical research, we consider glioma, non-small cell lung cancer and hepatocellular carcinoma as the most promising targets and propose investigating the effects on healthy tissue, especially neuronal cells and abdominal organs. The experimental setups for preclinical pMBRT used so far follow different technological approaches, and experience technical limitations when addressing the current questions in the field. We review the crucial physics parameters necessary for proton minibeam production and link them to the technological challenges to be solved for providing an optimal research environment. We consider focusing of pencil or planar minibeams in a scanning approach superior compared to collimation due to less beam halos, higher peak-to-valley dose ratios and higher achievable dose rates. A possible solution to serve such a focusing system with a high-quality proton beam at all relevant energies is identified to be a 3 GHz radio-frequency linear accelerator. We propose using a 16 MeV proton beam from an existing tandem accelerator injected into a linear post-accelerator, boosted up to 70 MeV, and finally delivered to an imaging and positioning end-station suitable for small animal irradiation. Ion-optical simulations show that this combination can generate focused proton minibeams with sizes down to 0.1 mm at 18 nA mean proton current being sufficient for all relevant preclinical experiments. This technology is expected to offer powerful and versatile tools for unleashing structured and advanced preclinical pMBRT studies at the limits and also has the potential to enable a next step into precision tumor therapy.